COPII genes SEC31A/B are essential for gametogenesis and interchangeable in pollen development in Arabidopsis. (1st February 2021) - Liu, Xiaoyu; Tong, Mengjuan; Zhang, Aiwei; Liu, Mei; Zhao, Bingchun; Liu, Zhaojiao; Li, Zhouyue; Zhu, Xu; Guo, Yi; Li, Rui
Summary: In eukaryotes, coat protein complex II (COPII) vesicles mediate anterograde traffic from the endoplasmic reticulum to the Golgi apparatus. Compared to yeasts, plants have multiple COPII coat proteins; however, the functional diversity among them is less well understood. SEC31A and SEC31B are outer coat proteins found in COPII vesicles in Arabidopsis. In this study, we explored the function of SEC31A and compared it with that of SEC31B from various perspectives. SEC31A was widely expressed, but at a significantly lower level than SEC31B . SEC31A‐mCherry and SEC31B‐GFP exhibited a high co‐localization rate in pollen, but a lower rate in growing pollen tubes. The sec31a single mutant exhibited normal growth. SEC31A expression driven by the SEC31B promoter rescued the pollen abortion and infertility observed in sec31b . A sec31asec31b double mutant was unavailable due to lethality of the sec31asec31b gametophyte. Transmission electron microscopy revealed that one quarter of male gametogenesis was arrested at the uninuclear microspore stage, while confocal laser scanning microscopy showed that 1/4 female gametophyte development was suspended at the functional megaspore stage in sec31a‐1/+sec31b‐3/+ plants. Our study highlights the essential role of SEC31A/B in gametogenesis and their interchangeable functions in pollen development. Significance Statement: Coat protein complex II (COPII) vesicles, coated by five different proteins, mediate transport from the endoplasmic reticulum to the Golgi apparatus in eukaryotes, and SEC31s are important outer coat proteins of the COPII complex. Here, we explore the functional diversity between Arabidopsis SEC31A and SEC31B. Though SEC31A/B have distinct expression patterns, they play interchangeable roles in pollen development at the protein level and are required for male and female gametophyte development.